Application Decision support System for superior and high Achieving using the Analytical Hierarchy Process Method - Indarso, Taruna Pratama; Taurusta, Cindy; suprianto, Suprianto (LPPM Institut Teknologi Telkom Purwokerto, 2025)
Traditional student selection methods often rely on subjective judgment, resulting in inconsistencies and potential biases. Therefore, a more systematic, objective, and efficient method is needed. The proposed system evaluates students based on four key criteria: religious competence, academic performance, extracurricular activities, and ethics. The Analytical Hierarchy Process (AHP) is used to assign priority weights to each criterion through a series of pairwise comparisons, facilitating a structured evaluation process. The Decision Support System (DSS) was developed using the Waterfall model, which includes stages of requirement analysis, system design, implementation, testing, and maintenance. Real student data from grades 7, 8, and 9 were used during system testing at Junior High School TPI Porong. This study aims to develop a mobile-based DSS to identify high-achieving students at Junior High School Taman Pendidikan Islam (TPI) Porong using the AHP method. The ranking results generated by the system were compared to manual evaluations conducted by teachers and showed over 90% consistency. Furthermore, a feasibility test involving 15 teachers indicated a 98.7% satisfaction rate, highlighting the system’s effectiveness and ease of use. The application presents rankings in a user-friendly interface, enabling teachers and school administrators to make informed decisions about student achievement. By implementing this system, schools can ensure a more transparent and data-driven process for selecting high-achieving students. The DSS not only improves the evaluation process but also supports the development of a fairer and more accountable education system. This research contributes to the advancement of technology-based educational tools that assist in decision-making within school environments.